A Novel Approach for Arteriovenous Fistula Maturation; Effects of Melatonin Loaded PLGA Nanofibers in Rats - Damla AYKORA; Serpil ŞAHİN; Cemre AYDEĞER; Özden YÜLEK; Sevil ALKAN; Ayhan ORAL; Muhammad Umar JAJERE (Namık Kemal Tıp Dergisi, 2025)
Aim: Arteriovenous fistula (AVF) is a cannulation method that is accessed by a peripheric vein and an artery. AVF provides vascular access for chronic kidney disease patients so they can receive hemodialysis. AVF could be created by surgical intervention and facilitates arterial to venous circulation for rapid recovery. However, AVF maturation depends on venous proliferation and luminal diameter which allows the optimum flow rate for continuing circiulation and hemodialysis. Due to multiple unexpected conditions, non-maturation of AVFs limits the efficacy of the hemodialysis so patients must receive another surgery for AVF cannulation. Materials and Methods: In this study, we aimed to utilize the effects of melatonin (MT), which is known to have antioxidant, anti-inflammatory, and antiapoptotic effects, to provide longer and more effective use of AVFs via a novel technique. For this purpose, firstly by electrospinning method, polylactic-co-glycolic acid (PLGA) nanofiber membranes were developed. After MT is loaded into the PLGA and characterized. Biodegradation and drug release profiles were analyzed. An in vivo study was performed in Wistar Albino male rats (n=18). Rats were randomly divided into three experimental groups; Sham, PLGA, and MT/PLGA respectively (n=6). AVF model was established in all groups between arteria carotica and vena jugularis under general anesthesia. The Sham group did not receive any treatment or biomaterial application. The developed membranes were placed onto the AVFs in PLGA and MT/PLGA groups. All rats were sacrificed on the 28th of the experiment. The anastomosis sites of all animals were harvested for histopathological analysis. Results: Our results showed MT/PLGA group indicated increased maturation levels conmpared to Sham group (p<0.05). Conclusion: The results showed that PLGA/MEL may be a promising material for early AVF maturation.